2020
DOI: 10.1097/md.0000000000019996
|View full text |Cite
|
Sign up to set email alerts
|

The association between Ki-67 expression and the clinical pathological characteristics of colorectal cancer

Abstract: Background: This study will explore the association between Ki-67 expression and clinical pathological characteristics (CPC) of colorectal cancer (CC). Methods: We will search relevant studies from electronic databases (Cochrane Library, PUBMED, EMBASE, Scopus, Cumulative Index to Nursing and Allied Health Literature, China Biology Medicine, and China National Knowledge Infrastructure) from beginning to April 1, 2020 without language and publication tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Owing to its role in cellular proliferation in all phases of the cell cycle except G0, it is strongly correlated to the overexpressed AKT due to regulating the tumor cell cycle from G1 to the S phase thus aggravating the proliferation levels of cancerous cells [ 48 ]. Li et al [ 49 ] indicated that abnormal activation of AKT and Ki-67 promoted colon cancer development and progression in addition to invasion and metastasis Considering the aforementioned data our results revealed a strong positive expression of Ki-67 in the tissues of rats with colon cancer which agree with the results of Xiao et al [ 50 ] who conducted a noticeable upregulated expression of Ki-67 in mice with colorectal cancer induced by AOM-DSS.…”
Section: Discussionsupporting
confidence: 91%
“…Owing to its role in cellular proliferation in all phases of the cell cycle except G0, it is strongly correlated to the overexpressed AKT due to regulating the tumor cell cycle from G1 to the S phase thus aggravating the proliferation levels of cancerous cells [ 48 ]. Li et al [ 49 ] indicated that abnormal activation of AKT and Ki-67 promoted colon cancer development and progression in addition to invasion and metastasis Considering the aforementioned data our results revealed a strong positive expression of Ki-67 in the tissues of rats with colon cancer which agree with the results of Xiao et al [ 50 ] who conducted a noticeable upregulated expression of Ki-67 in mice with colorectal cancer induced by AOM-DSS.…”
Section: Discussionsupporting
confidence: 91%
“…Immunohistochemical (IHC) staining is usually used to detect Ki-67, and the expression level of Ki-67 is related to cell proliferation activity, disease progression and cancer recurrence ( 7 ). Some studies have shown that Ki-67 is one of the prognostic indices of multiple solid tumors, such as nasopharyngeal carcinoma ( 8 ), stage I non-small cell lung cancer ( 9 ), gastrointestinal stromal tumour ( 10 ), and gliomas ( 11 ), resected triple-negative breast cancer ( 12 ), colorectal cancer ( 13 ), hepatocellular carcinoma ( 14 ), and thyroid cancer ( 15 ). Previous studies have shown an association between Ki-67 expression and melanoma patient prognosis, but the results have been contradictory ( 16 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our result also showed that CT 40keV in VP, Zeff in VP, IC in VP, and λ HU in VP were positively correlated with the expression of CRAC Ki-67. It has been speculated that this correlation can be attributed to the high expression of Ki-67 being related to the increase in tumor blood supply, which leads to a higher CT value on 40-keV VMI ( 1 , 17 ). Compared with other VMIs, 40-keV VMI exhibits the best signal-to-noise ratio and contrast-to-noise ratio ( 18 , 19 ), which can significantly improve the detection of lesions, as 40-keV is infinitely close to the 33-keV level of the iodine k edge ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is the third most common cancer in men and the second most common cancer in women, while having the highest cancer mortality in the world ( 1 ). The majority of CRC cases are colorectal adenocarcinoma (CRAC) ( 2 ).…”
Section: Introductionmentioning
confidence: 99%